HPLC-Analysis of Polyphenolic Compounds in Gardenia jasminoides and Determination of Antioxidant Activity by Using Free Radical Scavenging Assays - Riaz Uddin; Moni Rani Saha; Nusrat Subhan; Hemayet Hossain; Ismet Ara Jahan; Raushanara Akter; Ashraful Alam (Tabriz University of Medical Sciences, 2014)
Purpose: Gardenia jasminoides is a traditional medicinal plant rich in anti-inflammatory flavonoids and phenolic compounds and used for the treatment of inflammatory diseases and pain. In this present study, antioxidant potential of Gardenia jasminoides leaves extract was evaluated by using various antioxidant assays. Methods: Various antioxidant assays such as 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, reducing power and total antioxidant capacity expressed as equivalent to ascorbic acid were employed. Moreover, phenolic compounds were detected by high-performance liquid chromatography (HPLC) coupled with diode-array detection. Results: The methanol extract showed significant free radical scavenging activities in DPPH radical scavenging antioxidant assays compared to the reference antioxidant ascorbic acid. Total antioxidant activity was increased in a dose dependent manner. The extract also showed strong reducing power. The total phenolic content was determined as 190.97 mg/g of gallic acid equivalent. HPLC coupled with diode-array detection was used to identify and quantify the phenolic compounds in the extracts. Gallic acid, (+)-catechin, rutin hydrate and quercetin have been identified in the plant extracts. Among the phenolic compounds, catechin and rutin hydrate are present predominantly in the extract. The accuracy and precision of the presented method were corroborated by low intra- and inter-day variations in quantitative results in leaves extract. Conclusion: These results suggest that phenolic compounds and flavonoids might contribute to high antioxidant activities of Gardenia jasminoides leaves.